A micro scale study of climate change adaptation and disaster risk reduction in coastal urban strategic planning for the Jakarta. Issue 1 (18th November 2019) - Rahayu, Harkunti Pertiwi; Haigh, Richard; Amaratunga, Dilanthi; Kombaitan, Benedictus; Khoirunnisa, Devina; Pradana, Vito
Abstract : Purpose: This paper aims to describe an in-depth study that aimed to assess and develop a strategic disaster risk reduction plan to integrate climate change adaptation countermeasures in Cilincing, a North Jakarta City sub-district. Design/methodology/approach: The study used a back-casting approach to cover hazard assessment induced by increased susceptibility, as well as vulnerability, both as a baseline study and projected up to 2045 at the micro level. The urban village (Kelurahan) level is the unit of analysis. The capacity analysis is used as baseline data, which is reviewed against the trend of the hazard and vulnerability. Findings: The results of the study identify short-, medium- and long-term recommendations to integrate disaster risk reduction and climate change adaption. These include capacity building, especially emergency response capabilities, an increase of drainage capacity, improvements to transboundary management and minimising driving forces. Practical implications: These findings at the micro level are very important to present a more holistic and realistic strategy that can be implemented until 2045, but also provides a basis for up scaling into metropolitan region planning. Originality/value: This is a unique, micro-scale case study in the Cilincing sub-district of Jakarta that assesses and develops strategic disaster risk countermeasures and a reduction plan that integrates the effects of climate change, thereby addressing future disaster risk in Jakarta.